1997
DOI: 10.1183/09031936.97.10010156
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dipyridamole and theophylline on hypercapnic ventilatory responses: the role of adenosine

Abstract: The purine nucleoside, adenosine, has been implicated as a neuromodulator in central respiratory depression during prolonged exposure to hypoxia. It may also be a mediator of hypoxic hyperpnoea, acting on the carotid bodies. As there may be adenosine-sensitive mechanisms of hypoxic respiratory control, we sought to determine whether adenosine might be involved as a respiratory modulator in another central but non-oxygen-related control mechanism, the ventilatory response to hyperoxic hypercapnia.Twelve normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…But as mentioned before it is known that exogenous adenosine stimulates ventilation by activating the carotid bodies. [8][9][10]30,32,34 Considering the results of this study it seems possible that endogenous adenosine influences the HVR and the ventilatory drive. This reaction could help the organism to fight against hypoxia as adenosine is released within tissues under hypoxic conditions, because of increased tissue-ATP-depletion as a consequence of reduced oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…But as mentioned before it is known that exogenous adenosine stimulates ventilation by activating the carotid bodies. [8][9][10]30,32,34 Considering the results of this study it seems possible that endogenous adenosine influences the HVR and the ventilatory drive. This reaction could help the organism to fight against hypoxia as adenosine is released within tissues under hypoxic conditions, because of increased tissue-ATP-depletion as a consequence of reduced oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that theophylline did not however, posthypoxic hyperoxic ventilation did not differ with affect either the intercept of the extrapolation of hypercapnic and without theophylline. In addition, we have shown that almiventilatory response to zero ventilation (an index of apneic trine, a drug that is associated with a comparable increase in threshold) or the slope of the hypercapnic ventilatory response resting ventilation did not affect the posthypoxic hyperoxic venti- (34). Notwithstanding the uncertainty of extrapolation the ventilation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the uncertainty of extrapolation the ventilation (19). These data indicate that changes in resting ventilalatory response to CO 2 to below eupnea and that normal subjects tion, at least in the range observed in our study, may not be an were studied (34), these findings indicate that theophylline does important determinant of ventilatory poststimulus potentiation. not alter the CO 2 -mediated ventilatory control, rendering the Previous studies have shown that patients with periodic breathlikelihood of a selective action of theophylline on apneic threshing such as those with sleep apnea syndrome or brain damage old rather unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…theophylline (Hedner et al, 1982;Eldridge et al, 1985). On the other hand, adenosine stimulates breathing in conscious, unanesthetised humans (Fuller et al, 1987;Griffith et al, 1997). The depressant effect of adenosine on breathing in vivo is more potent during the time period around birth and/or is also more severe in anesthetised animals (Herlenius et al, 2002).…”
Section: Ballanyi K Atp Channels In Brain Hypoxiamentioning
confidence: 99%